2015
DOI: 10.1007/s11356-015-5749-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and polyphasic characterization of odor-producing cyanobacterium Tychonema bourrellyi from Lake Erhai, China

Abstract: The previous studies indicated that Tychonema-like strains from Lake Erhai could release geosmin so that the species was listed as the potential harmful cyanobacteria influencing the drinking water safety around Lake Erhai. But, the dynamics and biological information of this species were too limited. In this study, the polyphasic approach was used to reveal its biological characterization and the dynamics in Lake Erhai. The characters of trichomes, including filaments with solitary or bundle state, reddish-br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…As trichome width ranged from 6.8–8.9 µm in Tychonema from Lake Tegel, unequivocal species identification was not possible based on morphological characteristics alone. Genetic characterization of isolated strains may support species identification [ 30 , 31 ], but attempts to establish cultures were futile.…”
Section: Discussionmentioning
confidence: 99%
“…As trichome width ranged from 6.8–8.9 µm in Tychonema from Lake Tegel, unequivocal species identification was not possible based on morphological characteristics alone. Genetic characterization of isolated strains may support species identification [ 30 , 31 ], but attempts to establish cultures were futile.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanobacterial bloom problems in several lakes in China, including Lake Taihu, Chaohu, Erhai, and Dianchi, have attracted widespread concern from both the general public and the scientific community (Guo et al., 2022; W. Lu et al., 2017; H. Zhang et al., 2016). Our study not only confirmed the severe problems in these lakes but also further found that 103 of the 171 examined lakes have been affected by algal blooms in the past two decades, and many of these lakes suffer from comparable or even more severe blooms than those reported in other lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Some microalgae species, such as Chlorella and Spirulina, have been used in commercial production and utilization [18]. A large number of studies have shown the prospect of microalgae as a bioremediation technology [19], they can use wastewater organic matter as a carbon source and nutrient source, so that they can treat wastewater, and finally make algae culture cost-effective [20].…”
Section: Microalgaementioning
confidence: 99%